The Design of Hand Gestures for Selecting Virtual Objects. Issue 18 (8th November 2019) - Lin, Jeffrey; Harris-Adamson, Carisa; Rempel, David
ABSTRACT: Providing input for the selection of objects in virtual, augmented, and mixed-mode reality can be done with hand-held controllers or hand gestures depending on the complexity and precision required. Free hand gestures have the advantages of eliminating the need for a controller, not needing to see the controls on the controller, and potentially being less fatiguing. However, the designs of hand gestures for object selection have not been thoroughly evaluated for usability and performance. Eighteen participants evaluated four different ray-casting hand gestures (index thrust, index click, palm thrust, and palm click) and three snapback thresholds while selecting 2D targets of different sizes. Dependent variables were mean time to select targets, number of selections not completed, number of incorrect targets selected, and subjective preference. The index thrust and index click gestures were preferred by subjects and had faster mean selection times and lower number of incorrect target selections. There were no significant differences between snapback thresholds on productivity, error, or preference. Overall, the index thrust and index click gestures were associated with greater user confidence, particularly with smaller targets.